2017
DOI: 10.1128/iai.00148-17
|View full text |Cite
|
Sign up to set email alerts
|

Otitis Media and Nasopharyngeal Colonization inccl3−/−Mice

Abstract: We previously found CC chemokine ligand 3 (CCL3) to be a potent effector of inflammation during otitis media (OM): exogenous CCL3 rescues the OM phenotype of tumor necrosis factor-deficient mice and the function of macrophages deficient in several innate immune molecules. To further delineate the role of CCL3 in OM, we evaluated middle ear (ME) responses of ccl3 Ϫ/Ϫ mice to nontypeable Haemophilus influenzae (NTHi). CCL chemokine gene expression was evaluated in wildtype (WT) mice during the complete course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
3
9
0
Order By: Relevance
“…Another chemokine, CCL3, which inhibits the proliferation of immature progenitor cells but activates the proliferation of mature progenitor cells (Baba & Mukaida, 2014), was not potentiated in the NTHi infected ear fluids. The significance of CCL3 in protecting against NTHi-induced OM in mice is already known (Deniffel et al, 2017), and our data on CCL3 levels in both middle-ear fluids and serum suggests its role in inhibiting the infection of NTHi. Another important chemokine, CCL2, was elevated in the NTHi-infected mice.…”
Section: Nthi Infection In Preinflamed Middle Ear Causes Changes Insupporting
confidence: 61%
“…Another chemokine, CCL3, which inhibits the proliferation of immature progenitor cells but activates the proliferation of mature progenitor cells (Baba & Mukaida, 2014), was not potentiated in the NTHi infected ear fluids. The significance of CCL3 in protecting against NTHi-induced OM in mice is already known (Deniffel et al, 2017), and our data on CCL3 levels in both middle-ear fluids and serum suggests its role in inhibiting the infection of NTHi. Another important chemokine, CCL2, was elevated in the NTHi-infected mice.…”
Section: Nthi Infection In Preinflamed Middle Ear Causes Changes Insupporting
confidence: 61%
“…This study identified the major cellular pathways including TLRs, NOD-like receptors, and inflammasome genes that are activated during OM to control the host immune response. Using ccl3 −/− mice, Deniffel et al found that CCL3 plays a critical role in the bacterial clearance, inflammation resolution, and mucosal host defense [114]. Kurabi et al analyzed the phenotypes in Asc −/− mice and revealed the contribution of the inflammasome and IL-1β maturation in OM [115].…”
Section: New Insights Into Innate and Adaptive Immunity In Ommentioning
confidence: 99%
“…CCL3 is a chemoattractant for neutrophils, monocytes, dendritic cells and T cells [58,59]. This chemokine plays a role in the clearance of microbes such as influenza in the lung [60], murine cytomegalovirus in the liver and spleen [61], Klebsiella pneumoniae in the lung [62], and non-typeable Haemophilus influenzae in the middle ear [63]. CCL3 knockout mice have increased PVM loads in the lungs and reduced recruitment of immune cells, demonstrating this chemokine plays an important role in the control of PVM infection [64].…”
Section: Discussionmentioning
confidence: 99%